PENERAPAN ORIENTASI KEWIRAUSAHAAN TERHADAP KINERJA UMKM DENGAN TOTAL QUALITY MANAGEMENT SEBAGAI VARIABEL INTERVENING - Fella Sifa Khoviani; Khairina Nur Izzaty (Magister Manajemen STIE Bank BPD Jateng, 2020)
This study aims to determine the effect of the application of entrepreneurial orientation to the performance of MSMEs with total quality management (TQM) as an Intervening variable. In this study there are three variables, namely entrepreneurship orientation, TQM, and MSME performance. The population in this study is the food processing sector SMEs in the city of Semarang, with a sample of 64 respondents. The research model uses structural equation modeling (PLS-SEM) analysis which consists of an outer model and inner orientation on MSME performance, TQM has a positive effect on MSME performance, entrepreneurial orientation has a positive effect on TQM, and there is a positive influence on the role of TQM mediation in the application of entrepreneurial orientation to MSME performance.